2022
DOI: 10.1186/s12991-022-00419-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of social network as a coping strategy for depression among young people during the COVID-19 lockdown: findings from the COMET collaborative study

Abstract: Background Use of social media (SM) has exponentially grown particularly among youths in the past two years, due to COVID-19-related changing lifestyles. Based on the Italian COvid Mental hEalth Trial (COMET), we investigated the association between SM use and depressive symptoms among Italian young adults (aged 18–24). Methods The COMET is a nationwide multi-center cross-sectional study that investigated socio-demographic data, social networking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…One key-point observation from the study is the high prevalence of NSSI-related behaviors among the surveyed sample (which indeed comes from the general population and not a clinical sample), with a substantial percentage of participants who declared a current regular engagement in NSSIs (around two third of the sample) or a previous history of NSSIs (around 85% of the sample). These results highlight the urgent need for targeted interventions and support mechanisms to address the underlying psychological distress and maladaptive coping strategies prevalent among our current youth generation ( 4 ). These findings are indeed consistent with previous research carried out during the post-COVID-19 era which demonstrated a 2-/3-fold increase in NSSI, particularly among youngsters ( 23 25 ).…”
Section: Discussionmentioning
confidence: 96%
“…One key-point observation from the study is the high prevalence of NSSI-related behaviors among the surveyed sample (which indeed comes from the general population and not a clinical sample), with a substantial percentage of participants who declared a current regular engagement in NSSIs (around two third of the sample) or a previous history of NSSIs (around 85% of the sample). These results highlight the urgent need for targeted interventions and support mechanisms to address the underlying psychological distress and maladaptive coping strategies prevalent among our current youth generation ( 4 ). These findings are indeed consistent with previous research carried out during the post-COVID-19 era which demonstrated a 2-/3-fold increase in NSSI, particularly among youngsters ( 23 25 ).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, there is no in-depth discussion of the responsible use of social media [ 21 , 22 ], which would be of great interest. Neither are the positive points described, nor the opportunities they offer for communication and mutual support [ 65 ]. Given that the reality is that more and more children are using social networks to show their discomfort [ 66 ], it is of greater interest to focus efforts on how to take advantage of this reality for prevention and treatment interventions, rather than blanket criticism.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is research evidence that social media use contributes to the overall ability of older adults to engage more fully and effectively in social contexts, thereby enriching their social well-being and interactions 50 . Moreover, during the COVID-19 pandemic, several studies observed that social media usage ameliorated some of the social isolation produced by lockdowns in youth 51 , while adolescents who did not have access to a computer experienced substantially worsened mental health outcomes over that period 52 .…”
Section: From Nurturing Connections To "Fear Of Missing Out"mentioning
confidence: 99%